KARAKTERISTIK WISATAWAN YANG MENJADI KORBAN TINDAK KRIMINALITAS DI KAWASAN WISATA SANUR DAN SEKITARNYA - Puspitasari, Ni Komang Meida; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 2 No 2 (2014): VOL 2, NO 2 (2014): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2014.v02.i02.p06, 2014)
ABSTRACT Sanur tour region is one of popular destination in Bali. As a tour region, security of this place must be so important to make the tourists feel save when go on vacation. Criminal action usually attack the foreign tourist than local tourists. Criminal action presume that foreign tourists always bring a lot of money for their vacation. This study discusses about tourist characteristic that being victims of criminal action. In order to know which characterictic of tourists that attack by criminal action. This study used descriptive qualitative method which has qualitative and quantitative data. Data collected by observation, in-depth interviews with purposive sampling approaches, literatures, and documentation. This study has definition operational variable that are age, nationality, sex, religion, profession, and sort of criminal action that consist to the tourists. The stakeholder of Sanur tour region already makes serious effort to guard their region security. But Sanur tour region still consists the criminal action that attack foreign tourist from France, Dutch, and Japan. In this study, also submitted suggestions based on discussions that the stakeholder in Sanur needs to improve their security to guard Sanur area as a tour region for tourists.
Keywords: Characteristics, victims, crime, and visitor.